Leemos un periódico mural - Zavaleta Blas, Luz Felipa (2019)
The learning session "we read a mural newspaper" which is presented below, was applied in the_x000D_ communication course for first grade students of high school, in the Rafael Narvaez Cadenillas_x000D_ Experimental Educational Center._x000D_ Considering the theoretical scope within the psychopedagogical and scientific field related to the_x000D_ subject, the development of an effective teaching - learning process is proposed, with the purpose of_x000D_ achieving a significant learning of the study of the subject._x000D_ Subsequently, and having achieved the main objective of this session, the students will have learned_x000D_ about the mural newspaper: definition, characteristics, sections and importance. So, they will be able_x000D_ to identify the characteristics of a mural newspaper, its importance as media and the way in which it_x000D_ presents diverse information on a topic or several topics of collective interest.